The Influence of Supply Chain Practices and Performance Measurement Practices towards Firm Performance - Frank Augustine Elisha Mkumbo; Abdul Razak Ibrahim; Abdul Latif Salleh; Veera Pandiyan Kaliani Sundram; Atikah Shamsul Bahrin (International Journal of Supply Chain Management, 2019)
The assessment of the success of organizations throughout history has been done using performance metrics. Performance measurement quantifies effectiveness and efficiency of action using metrics. Proper selection of key performance variables allows for major consideration in improvement, problem identification, and gauging performance against plans, norms, or best practices, and so giving directions for improvement plans. The concept paper predicts that supply chain management is practical in developing economies and to improves performance of organizations in the chain. Furthermore, it hopes to help firms that embraced supply chain management to used balanced sets of measures coupled with appropriate performance measurement practices (PMP) to increase performance results. Additionally, the proposed framework will be useful in any environment as it resulted from the synthesis of past literatures and studies. This study is one of the first to identify and discuss conceptually the relationship between performance measurement practices and overall firm performance.